A novel biodegradable injectable chitosan hydrogel for overcoming postoperative trauma and combating multiple tumors. (1st August 2021) - Wang, Wentao; Zhang, Qicheng; Zhang, Ming; Lv, Xintong; Li, Zihan; Mohammadniaei, Mohsen; Zhou, Ninglin; Sun, Yi
Highlights: CS@BPNSs@CuNPs can help postoperative hemostasis (24.98 %) and catch residual cells. The hydrogel generated high ROS for antibacterial (98.1 %) and anticancer (11.3 %). The combination of hydrogel and aPD-L1 showed a synergistic therapeutic effect. The biodegradable hydrogel could cross blood tumor barrier to treat glioblastoma. Abstract: Wound bacterial infections and tumor recurrence are the main reasons for the poor prognosis after primary tumor resection. Here, we fabricated a novel therapeutic nanocomposite using chitosan (CS) hydrogel combined with black phosphate nanosheets (BPNSs) and in situ grown copper nanoparticles (CuNPs). The obtained hydrogel (CS@BPNSs@CuNPs), possessing a remarkable temperature-sensitive spongy-like state, offered 24.98 % blood clotting index. The released BPNSs@CuNPs could produce reactive oxygen species (ROS) to kill infected invasive bacteria (98.1 %) and inhibit local residual tumor cell regeneration (11.3 %). Moreover, by coupling the photothermal properties of BPNSs, the BPNSs@CuNPs showed 19.6 % penetration rate to cross the blood tumor barrier (BTB) for treating brain tumors. The hydrogel platform was further combined with aPD-L1-based immunotherapy to employ its synergetic therapeutic effect in the prevention of tumors. The in vivo studies showed that biodegradable hydrogel could hold a great potential as a novel strategy for improving postoperative therapy and multi-tumor treatments.